FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA HOUSEKEEPING DEPARTMENT DI HOTEL IBIS PEKANBARU - Sofial, Nidea Rezka; Rifyan, Andi M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this research was to investigate the implementation of standard operating procedre by housekeeping department of hotel Unigraha Pangkalan Kerinci. Hotel Unigrah in increasing the number of the guests. And the guest feedbeack on the implementation of standard operating proedureThis research uses therory of Bagyono(2008) to explanation on the implementatioan of housekeeping Department,standard operating proccedure by room boy Hotel Uniigraha Pangkalan Kerinci.Base on the result of, responden to the faktors that effect the performance of housekeeping department at the hotel ibis pekanbaru,are namely organizational factors, individual faktors and social faktors. Where the organizational faktors that most influence significanly.This method of this research is using qualitative descriptive analysis method.Anaysisi in this research based on literature,observation and direct wiew with informan who consider able to provie information relating to problem exmined.The number of the guest visits of Hotel Unigraha.It canno be separated efforts to implementat the standar of operating procedure by Room boy and be barrometer succes of standard operating procedure has been done.Key words : implementtation,standard operating procedre,housekeeping androom boy